Hormonal Changes in Puberty - Teshayeva Zarnigor (Genius Journals, 2022)
This article discusses hormonal changes, psychological and physiological conditions observed in individuals who have reached puberty and are on the verge of adolescence.
Keywords: hormonal change; adolescent; psychology; condition